2019
DOI: 10.1186/s12933-019-0893-2
|View full text |Cite
|
Sign up to set email alerts
|

Triglyceride-glucose index is associated with symptomatic coronary artery disease in patients in secondary care

Abstract: Background The triglyceride-glucose index (TyG index) is a tool for insulin resistance evaluation, however, little is known about its association with coronary artery disease (CAD), which is the major cardiovascular death cause, and what factors may be associated with TyG index. Objective To evaluate the association between the TyG index and the prevalence of CAD phases, as well as cardiovascular risk factors. Methods The baseline data of pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
153
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(161 citation statements)
references
References 42 publications
5
153
1
2
Order By: Relevance
“…Few studies have reported associations between a high TyG index and the presence of coronary artery complications in type 2 DM and healthy adults [12,15,52]. In this study, we did not find a statistically significant association between the TyG index and CAD in the patients with type 2 DM.…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…Few studies have reported associations between a high TyG index and the presence of coronary artery complications in type 2 DM and healthy adults [12,15,52]. In this study, we did not find a statistically significant association between the TyG index and CAD in the patients with type 2 DM.…”
Section: Discussioncontrasting
confidence: 84%
“…Recently, the triglyceride-glucose (TyG) index was proposed as a simple and reliable surrogate marker of IR, and it has been reported to be closely correlated with the HOMA-IR index [8][9][10]. Previous clinical data have shown associations of the TyG index to the atherosclerotic cardiovascular diseases, including carotid atherosclerosis [11], coronary artery calcification [12], arterial stiffness [13,14], and CVD [15][16][17][18]. Additionally, our previous study showed that a higher TyG index was associated with an increased risk of cardiovascular events among patients with type 2 DM [19].…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies reported that the TyG index was related to the risk of developing traditional CV disease and adverse clinical events. Recent cross-sectional data from Brazilian Cardioprotective Nutritional Program Trial showed the positive association of TyG index with metabolic and behavioral risk factors [27]. In the present study, we identified that the incidence of CAC progression was elevated with an increasing TyG index irrespective of baseline CACS in this study.…”
Section: Discussionsupporting
confidence: 66%
“…Previous studies have shown that the TyG index may predict the development of type 2 diabetes mellitus [12] and metabolic syndrome [13]. It has been reported that the TyG index is positively associated with the higher prevalence of subclinical coronary artery disease (CAD) [14], symptomatic CAD and metabolic and behavioral risk factors [15], and arterial stiffness and nephric microvascular damage [16]. Moreover, higher TyG index correlated with increased risk of main adverse cardiovascular and cerebrovascular events (MACCE) in acute ST-elevation myocardial infarction (STEMI) patients, and the TyG index might be a valuable predictor of clinical outcomes in STEMI patients undergoing percutaneous coronary intervention [17].…”
Section: Tyg Index and The Severity And Mortality Of Covid-19mentioning
confidence: 99%